Soroprevalência e caracterização genética de estirpes de campo do vírus da anemia infecciosa equina em equídeos errantes do estado do Rio Grande do Norte - Câmara, Rebeca Jéssica Falcão (2017)
Equine infectious anemia (EIA) is the most important viral disease among horses. It is an endemic disease in populations of Equidae throughout the world. All equids are considered to be susceptible although most of the published work are focused in horses, with a lack of information on EIA in donkeys. In the State of Rio Grande do Norte, Brazil thousands of donkeys live free, establishing a problem for the control of diseases like the EIA, since they may play a role as reservoirs. In this work, blood samples taken from 409 animals (asinine and equine) were submitted to IDGA, ELISA pgp45 and nested-PCR tests, using gag and LTR gene as molecular markers. Four samples (0.98%) were positive in at least one serological test, and of these, three (0.73%) were positive to nested-PCR. We did not get enough material for sequencing of LTR samples from asinine, then only the amplified referring to the positive equine sample was sequenced. The alignment (BLAST) allowed the identification of the sequence as EIAV with 95% of similarity with european strains. Three product from nested-PCR products for the gag gene were sequenced and submitted to phylogenetic analysis. The result of this analysis suggested that the samples obtained from the horse had the same origin as strains from North America, and that the sequences from donkey samples had no homology with any other already published available EIAV sequence. In the light of the results from this work, additional studies are required. So we could confirm that we found a new strain of EIAV or endogenous retrovirus that are capable of expressing genes that are homologous to EIAV or even a new species of lentivirus Although the presented data are incomplete, they reveal an interesting scenario for the study of EIAV infection in equids ther than the horses